Does Financial Constraints Matter to Youth Entrepreneurship in Kathmandu? - Narayan Prasad Aryal,; Elmira Siska,; Gobind Kumar Singh, (Interdisciplinary Journal of Management and Social Sciences, 2025)
This study aims to investigate the financial barriers faced by young entrepreneurs in Kathmandu. A quantitative methods approach was employed. The survey targeted a sample of 215 young entrepreneurs, while in-depth survey were conducted with participants to gain deeper insights into their experiences with accessing finance. The result showed that entrepreneurial skill has significant positive relationship with youth entrepreneurship development. Likewise, rules and regulation has a positive and significant effect. Similarly, access to finance showed a significant positive contribution to youth entrepreneurship development. Education and training demonstrated a positive and statistically significant impact on youth entrepreneurship development in Kathmandu. The study concludes that financial barriers severely limit the potential for youth entrepreneurship in Kathmandu. Without adequate financial support and resources, young entrepreneurs struggle to establish and maintain viable businesses. The findings underscore the need for targeted policies that enhance access to financial resources for young entrepreneurs, such as microfinance options and government-backed loans. Furthermore, promoting entrepreneurial education and training can empower youth to navigate these challenges effectively, ultimately contributing to economic growth in Nepal.